KOMUNIKASI INTERPERSONAL ANTARA IBU TIRI DAN ANAK DALAM MEWUJUDKAN HUBUNGAN YANG HARMONIS - Genis, Chintya; Rimayanti, Nita (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The harmonious relationship is crucial within the family between the stepmother and the child. This is due not to the occurrence of jealousy, conflict, and misunderstandings between the stepmother and the child. In raising this harmonious relationships in need the role of the stepmother and the child, because the child's stepmother and peraanan is very helpful in enhancing the harmonious relationships. Interpersonal communication is a dialogue conducted between individuals or groups with specific goals and how to get the desired results. This research aims to find out how the interpersonal communication between the stepmother and the child in improving harmonious relationships. This research uses qualitative research methods. Informants in this study 3 stepmother and 3 children. Data collection techniques with the use of observation, interview and documentation. In pursuit of the validity of the data in this study, researchers using 2-opt and triangulation. The results showed that interpersonal communication is done the stepmother and the child is doing well. As for the element of kerberhasilan enhance harmonious relationships between the stepmother and the child include the following: first, the existence of openness that is the willingness of the stepmother and son exchanged thoughts with each other. Second, the empathy that is visible from the stepmother attempts to feel what the children feel, and understand the opinions and attitudes of children, and vice versa are also trying to feel what her stepmother feel and understand the opinions and attitudes of the stepmother.Third, supporting attitude that is by encouraging and motivating for children's stepmother in the activities of the day-a day. Fourth, a positive attitude that is shown with positive feelings and thoughts without any prejudice and suspicion between the stepmother and the child. Fifth, the equality that is by putting a position equivalent to older stepmother in conveying the message.Sixth, conflict management, namely the ability of the individual to manage the conflicts in its proper way, with a strategy of effective conflict with attitudes in sportsmanship, in managing the conflict and in the dukunganya attitude of openness in between them then the relationship that is created between the stepmother and the child the more harmony and conflict between them was resolved with the absence of the misunderstanding between them.